Experimental Study on the Effect of Combination of Thermodynamic Inhibitors’ and Kinetic Inhibitors’ Hydrate Inhibition - Gao, Yonghai; Wang, Yanlong; Xin, Guizhen; Wang, Xiangdong; Yue, Cheng; Chen, Litao (Frontiers in Energy Research, 2021)
In deepwater gas well testing, the high-pressure and low-temperature environment in the wellbore provides conditions for hydrate formation. When the thermodynamic inhibitor is used, it needs a large amount and is difficult to inject. Low-dose hydrate inhibitors such as kinetic inhibitors are rarely used in high supercooling and natural gas–dominated environments. The mixed use of thermodynamic inhibitors and kinetic inhibitors provides a new way. By simulating the wellbore temperature and pressure conditions during the deepwater gas well testing, the inhibiting effect of the mixtures of PVCap and methanol with various concentrations was experimentally tested by using rocking cells with a step-cooling method at 21MPa. The effect of PVCap and its mixture with methanol on hydrate plugging was evaluated by monitoring the movement of slider in the rocking cell. The results showed that 5 wt%, 16 wt%, and 20 wt% methanol mixed with 0.5 wt% PVCap could prolong the induction time, and the higher the methanol concentration, the longer the hydrate induction time. Among them, the best combination of 20wt% methanol and 0.5wt% PVCap can inhibit the hydrate for 379 min. The hydrate was formed but did not block the rocking cell, indicating that the combination of PVCap and methanol could not only prolong the hydrate formation time but also avoid the blockage after hydrate formation. The hydrate formation rate with various inhibitor concentrations was calculated; it may provide some guidance for making a shut-in plan for on-site wells.